Collaborative learning activities among TESL / ESL undergraduates - Asmah, bt Abdul Hamid. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The purpose of this study was to investigate the TESLIESL undergraduates' perception towards collaborative learning and to what extent it affects the students' cognitive and social skills. One 28-item questionnaire including 2 open-ended questions was administered to 150 TESLIESL undergraduates that were picked randomly in UNIMAS who made up the samples of the study. Descriptive statistic 'was used for this study to analyze the percentages and the mean scores. The findings showed that TESLIESL undergraduates had positive perception towards collaborative learning. The findings of this study also indicated that collaborative learning affect on students' cognitive and social skills. Based on the development of students' cognitive and social skills in collaborative learning, some other important issues needed to be discussed for further research in order to explore more about collaborative learning.